2018
DOI: 10.1093/neuros/nyy065
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation for the Treatment of Chronic Pain Reduces Opioid Use and Results in Superior Clinical Outcomes When Used Without Opioids

Abstract: Sixty-four percent of patients who were using opioids prior to SCS reduced (n = 2) or eliminated opioid use (n = 29) at 1 yr postoperatively. Patients who eliminated opioid use or never used opioids had superior clinical outcomes to those who continued use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 28 publications
0
31
1
Order By: Relevance
“…Conventional SCS treatment has been shown to be associated with reduction in conventional opioid dose and stabilization of usage in two large retrospective studies by Sharan et al and Simopoulos et al 33,34 Multiple systematic reviews also demonstrated increased odds of reducing pain medication in patients with intractable pain follow-ing SCS treatment. 35,36 Considering the potential advantages of 10 kHz SCS, this review was conducted to summarize the current landscape of evidence in the medical literature regarding the efficacy of 10 kHz SCS to both treat pain symptoms and reduce the amount of conventional opioid analgesics required by patients with chronic, noncancer pain.…”
Section: High-frequency Scs At 10 Khz (Hf10)mentioning
confidence: 99%
“…Conventional SCS treatment has been shown to be associated with reduction in conventional opioid dose and stabilization of usage in two large retrospective studies by Sharan et al and Simopoulos et al 33,34 Multiple systematic reviews also demonstrated increased odds of reducing pain medication in patients with intractable pain follow-ing SCS treatment. 35,36 Considering the potential advantages of 10 kHz SCS, this review was conducted to summarize the current landscape of evidence in the medical literature regarding the efficacy of 10 kHz SCS to both treat pain symptoms and reduce the amount of conventional opioid analgesics required by patients with chronic, noncancer pain.…”
Section: High-frequency Scs At 10 Khz (Hf10)mentioning
confidence: 99%
“…Most recent studies on patients with chronic pain that had SCS implanted showed either a significant reduction of opioid consumption4 or no change in opioid consumption a year after SCS implantation 5. Results of your study showed that patients that are current smokers even had escalated opioid consumption after 1 year of SCS implantation.…”
mentioning
confidence: 77%
“…There is currently an opioid epidemic in the United States so SCS may be a promising alternative to long‐term opioid therapy in some patients. A US study found that 64% of patients who were using opioids prior to SCS reduced or eliminated opioid use one year later . Another US study also found that spinal neuromodulation can stabilize (23%) or decrease (47%) opioid usage .…”
Section: Discussionmentioning
confidence: 99%